Evaluating Performance of Photographs for Marine Citizen Science Applications - Newcomer, Katherine; Tracy, Brianna M.; Chang, Andrew L.; Ruiz, Gregory M. (Frontiers in Marine Science, 2019)
Long-term measurements are imperative to detect, understand, and predict changes in coastal biological communities, but can be both costly and difficult to implement. Here, we compare measurement methods used to document community structure and assess changes in marine systems, and explore potential applications in citizen science. The use of photographs for species identifications and monitoring has become a popular and useful data collection tool, but its use requires evaluation of its effectiveness in comparison to data collected from live examinations. We used settlement panels in San Francisco Bay, a well-studied and vital coastal ecosystem, to compare standardized measures of the invertebrate fouling community through examination of live organisms in the field and via photographs. Overall, our study found that live measurements were more accurate and better represented these marine communities, having higher richness and diversity measurements than photographic measurements. However, photographic analyses accurately captured the relative abundances of some species and functional groups. We suggest that highly recognizable target taxa or broad scale comparisons of functional group composition are easily tracked through photographs and offer the best potential for research conducted by citizen scientists.